Supine Percutaneous Nephrolithotomy Under Spinal Anaesthesia: Our Experience Of 365 Cases - Muhammad Nasir Jamil, Muhammad Asif, Hamza Ashraf, Ehsan-ul-Islam, Akbar Azam, Romana Bibi (Pakistan Journal of Medical & Health Sciences, 2023)
Aim:To determine the safety and efficacy of supine PCNL under spinal anesthesia (SA). Methods: It’s a review of secondary data of 365 caseswho underwent supine PCNL under Spinal anesthesia from April 2015 to December 2021. We determined the Outcomesof the procedure in terms of the operation time,stone clearance rate, hospital stay, analgesia requirements,and perioperative complications rate. Results: Out of 365patients 66.3% were male and the rest were female. The mean age was 47.80 ± 10.46 SD and the mean stone size was 3.4 cm±1.04 SD.Multiple or staghorn stones were found in 57.3% of cases. The majority of stones 57.5% were located in the renal pelvis and calyces. The mean operation time was 65 min ± 2.9 SD, and the stone clearance rate was 87%. Analgesia after surgery was given in 23% of the cases. Fever was noted in 11.23%, and blood was transfused in 3.5% of cases. No case of urinary leakage was observed and angioembolizationwas not needed in any case. The complications associated with spinal anesthesia were spinal headache in 3.56%, hypotension in 3%,and nausea and vomiting in 1.56% of the cases. Conclusion: Supine PCNL under spinal anesthesia is associated with good clinical outcomes lesser operative time and fewercomplications. Moreover, it is cost-effective as well. Keywords: Percutaneous nephrolithotomy, supine position, spinal anesthesia